Vancouver School of Art : The Growth Years, 1939-1965. - Lindberg, Theo; Emily Carr College of Art, Granville Island, Vancouver (Vancouver : Charles H. Scott Gallery, 1983)
Amess, Fred ; Aspell, Peter ; Bergthorsen, Chris ; Binning, B.C. ; Bobak, Bruno ; Bond, Richard ; Branscomb, Keith ; Breeze, Claude ; Cooter, Paddy ; Derreth, Reinhard ; Dixon, Reg ; Capel Doray, Audrey ; etc.
Vancouver School of Art : The Growth Years, 1939-1965, The Charles H. Scott Gallery, Emily Carr College of Art and Design, Vancouver, April 8 through May 3, 1983
English
kunstcatalogus